Development and analysis of direct current low energy micro-sheet-forming machine - Chang, Tai Ann (2016)
Increased demands for micro-products have led to rapid development of micro-manufacturing technologies in the manufacture of individual parts and systems, which includes development of new manufacturing processes, tools and machinery. Tremendous efforts have been made, to date, to improve the efficiency of miniature-/ micro-manufacturing technologies. However, there has been lack of research on energy saving during which materials are being processed. It is expected that with the miniaturization of materials being processed, energy consumption is also being ‘miniaturized’ proportionally. The focus of this study was to design a low energy micro-sheet-forming machine for thin sheet metal application and fabricate a low direct current powered micro-sheet-forming machine. In addition, the research aimed to quantify and analyze the capability and quality of the fabricated machine. Several concepts were generated and these were evaluated by performing Finite Element Method (FEM) analysis and materials comparison. An optimal concept was selected to develop a detailed design. Fabrication and assembly of the machine was made according to the selected conceptual design. A prototype of low energy system for a micro-sheet-forming machine that included mechanical and electronic elements was developed. The machine was tested for its performance in terms of natural frequency, punching forces, punching speed and capability, energy consumption (single punch and frequency-time based). The machine was capable of single stage of micro-sheet-forming processes for thin sheet metal parts with thickness of less than 100 μm. Furthermore, it was also capable of producing up to 600 strokes per minute, with force capacity of 320 N. The energy consumption for the machine to produce a single part was 0.0038 Wh. Thus, it can be concluded that this research has successfully resulted in the development of a low energy micro-sheet-forming machine for thin sheet metal forming application.